Enhancing English Spelling Errors in Writing Composition Among ESL Learners - S.M. Hakeema Beevi; M.J.F Sujani; MB Nowzath; MR. Rishad Muhammed (COMPETITIVE: Journal of Education, 2025)
This study investigated the major English spelling errors committed by second language learners of KM/STR-Sennal Zahira Maha Vidyalaya. The school students face problems and get under-sired marks in exam in pre and post-test. The study identifies substitution, omission, Transposition and insertion errors committed by L2 learners and the effective strategies to overcome such research through the intervention process. For conducting this research, the mixed method was adopted and the data was collected from 27 students of class ‘A’ of grade Eleven of KM/STR-Sennal Zahira Maha Vidyalaya. Students were requested to write the exam that SQ, and essay writing of 50 words on selected topic and also dictation test was conducted later spelling errors were detected and differentiated into the types of spelling errors. Moreover, three English language teachers were interviewed to know the factors and effective strategies to overcome spelling errors. The quantitative data was analyzed by marks and percentage and qualitative data was analyzed by cording method. The findings indicated that mostly second language learners at KM/STR-Sennal Zahira Maha Vidyalaya (G.C.E O/level students) committed with sound based spelling errors related with substitution (consonant to consonant and consonant to vowel) and omission. However, through teaching process in post-test students enhanced their knowledge of spelling of words by 27%. Finally, students and teachers need mechanism and awareness about spelling errors that can greatly impact their quality writing without spelling mistakes or errors.